2019
DOI: 10.3389/fonc.2019.01069
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles for HBV Related Hepatocellular Carcinoma Including Alpha-Fetoproteins Positive and Negative Subtypes

Abstract: Background: Hepatocellular carcinoma (HCC) is very common globally prevalent cancer. Due to its poor clinical prognosis, increasing the diagnostic rate of HCC is urgently needed. Herein, we validate discovered metabolomic biomarkers to distinguish Hepatitis B virus (HBV)-related HCC, including alpha-fetoprotein (AFP) negative (AFP–) and positive (AFP+) individuals.Methods: We recruited 130 HCC subjects (independent case-control, randomized clinical cohorts) to our study. We separated the subjects randomly into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Liu et al concluded that des-gamma-carboxyprothrombin (DCP) can distinguish AFP-negative HBV-related HCC from chronic HBV infection (AUC = 0.731) or LC (AUC = 0.685) 48 . Several studies have attempted to combine multiple biomarkers [54][55][56][57][58][59][60][61] or serological examinations [62][63][64][65][66] . With the help of proteomics technology, researchers have identified some abnormally expressed proteins that were verified in various cancers [67][68][69][70] to construct a logistic regression model, which had good performance in distinguishing AFP-negative HCC 60 .…”
Section: Afp Is Used As a Biomarker In Hccmentioning
confidence: 99%
“…Liu et al concluded that des-gamma-carboxyprothrombin (DCP) can distinguish AFP-negative HBV-related HCC from chronic HBV infection (AUC = 0.731) or LC (AUC = 0.685) 48 . Several studies have attempted to combine multiple biomarkers [54][55][56][57][58][59][60][61] or serological examinations [62][63][64][65][66] . With the help of proteomics technology, researchers have identified some abnormally expressed proteins that were verified in various cancers [67][68][69][70] to construct a logistic regression model, which had good performance in distinguishing AFP-negative HCC 60 .…”
Section: Afp Is Used As a Biomarker In Hccmentioning
confidence: 99%
“…The detection of disease-related molecules in blood is simple and non-invasive and is widely regarded as the best choice for disease screening and diagnosis. In recent years, many biomarkers in blood have been identified and evaluated for the diagnosis of ANHC ( Figure 1 ), such as genetic biomarkers, proteins, and also metabolic biomarkers ( 31 ).…”
Section: Blood Biomarkers For Anhc Diagnosismentioning
confidence: 99%
“…However, the majority of these potential candidates still have shown poor specificity and sensitivity in extending independent validation. 11,12 Des-gamma-carboxyprothrombin (DCP) was once proposed to be a better HCC diagnostic marker, investigations have reported that the area under the receiver operating characteristic (AUC) of DCP is only 0.731 for diagnosing ANHCC. 13 Some other biomarkers including glypican-3, 14 Golgi protein-73 15 and micro-RNAs 16 are promising for ANHCC monitoring.…”
Section: Introductionmentioning
confidence: 99%